Metabolomic profiling and antimicrobial investigation of Aspergillus fumigatus LBKURCC269 and Bacillus paramycoides LBKURCC218 co-culture - Octarya, Zona; Nugroho, Titania T.; Nurulita, Yuana; Suraya, Nabella; Saryono, Saryono (Narra Sains Indonesia, 2025)
The increasing resistance of pathogenic microbes to antibiotics is a major public health concern, necessitating the discovery of effective antimicrobial compounds. The aim of this study was to assess the bioactive metabolites produced by Aspergillus fumigatus LBKURCC269 and Bacillus paramycoides LBKURCC218 under three fermentation conditions: monoculture of each microorganism and their co-culture. Metabolite analyses initiated with gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-high-resolution mass spectrometry (LC-HRMS) followed with molecular networking–Global Natural Products Social Molecular Networking (GNPS) and molecular docking. Antimicrobial activity of the extracts was then conducted. Metabolite analysis using GC-MS identified key antimicrobial compounds, including 2,6-bis(1,1-dimethylethyl)-4-methylphenol, pentadecanoic acid, cyclopropane pentanoic acid, and 3-piperidinol. LC-HRMS, combined with multivariate analysis and GNPS molecular networking, revealed additional antimicrobial compounds, including novel pyrazine derivatives induced in co-culture fermentation. Molecular docking analysis of 3-(propan-2-yl)-octahydropyrrolo[1,2-a]pyrazine-1,4-dione demonstrated its potential as an antimicrobial agent by inhibiting topoisomerase IV and cytochrome monooxygenase with binding affinity of -5.34 kcal/mol and -5.6 kcal/mol, respectively. The antimicrobial assays showed that the co-culture fermentation extract had the strongest activity, with inhibition zones of 20.33±0.59 mm (Escherichia coli), 14.33±0.59 mm (Staphylococcus aureus), and 25.67±0.59 mm (Candida albicans). This study highlights the advantages of co-culture fermentation in enhancing the discovery of antimicrobial compounds. The findings underscore the potential of this approach to simplify chemical isolation and accelerate the identification of novel antimicrobial agents for pharmaceutical development.